A Temporal Analysis of Quarterly Earnings Thresholds: Propensities and Valuation Consequences - Brown, Lawrence D.; Caylor, Marcus L. (The Accounting Review, 2005)
Applying a Burgstahler and Dichev (1997)/Degeorge et al. (1999) type methodology to quarterly data for the 1985–2002 time period, we show that, since the mid-1990s, but not before then, managers seek to avoid negative quarterly earnings surprises more than to avoid either quarterly losses or quarterly earnings decreases. Our findings suggest that the quarterly earnings threshold hierarchy proposed by Degeorge et al. (1999) does not apply to recent years, and that managers' claim that avoiding quarterly earnings decreases is the threshold they most seek to achieve (Graham et al. 2004) is inconsistent with their actions. We provide an intuitively appealing economic rationale for why the shift in threshold hierarchy occurred; since the mid-1990s, but not before then, investors unambiguously rewarded (penalized) firms for reporting quarterly earnings meeting (missing) analysts' estimates more than they did for meeting (missing) the other two thresholds. We provide several explanations for why investors unambiguously reward firms for reporting quarterly earnings that meet or beat analysts' estimates more than for meeting the other two thresholds late (but not early) in our sample period: increased media coverage given to analyst forecasts, more analyst following, more firms covered by analysts, and temporal increases in both the accuracy and precision of analyst forecasts.